KIPCHAK ETHNONYMS IN THE “TALE OF BYGONE YEARS” - AKHMETOVA, Zhanculu; KAIRZHANOV, Abay K.; KAIRZHANOV, Abay K.; ILYASSOVA, Zibagul; Bibikhadisha; Abzhapparova, Zh.; Otelbay, Gulbaira T. (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the ethnonymy of the Polovtsian field, the tribal composition of which received different names in the space of the Great Steppe: Kipchaks, Polovtsy, Cumans (comans). The methods and techniques of hermeneutics, semantic analysis and the comparative historical method are used to determine how certain Kipchak ethnonyms with the totemic component were formed. The semantics of the totemic components of ethnonyms are revealed and their reflexes and rudiments are determined, reflecting the ancient mythology of the nomads of the primitive era. In addition, some symbols are imprinted in the patterns and ornaments on some clothes of the Kipchak peoples. The zoomorphic images of the Kipchaks are analyzed, and it is revealed that these images are equipollent with similar images of other ethnic groups, and at the same time it is determined that they form part of the universal human culture of Eurasia.